LncRNA IL21‐AS1 interacts with hnRNPU protein to promote IL21 overexpression and aberrant differentiation of Tfh cells in systemic lupus erythematosus. Issue 12 (29th November 2022) - Liu, Limin; Hu, Longyuan; Long, Haojun; Zheng, Meiling; Hu, Zhi; He, Ye; Gao, Xiaofei; Du, Pei; Zhao, Hongjun; Yu, Di; Lu, Qianjin; Zhao, Ming
Abstract: Background: The aberrant differentiation of T follicular helper (Tfh) cells plays an important role in the pathogenesis of systemic lupus erythematosus (SLE). However, the mechanism of regulating Tfh cells differentiation remains unclear. Long noncoding RNAs (lncRNAs) act as important regulators in the processes of innate and adaptive immune response. Whether lncRNAs are involved in regulating Tfh cell differentiation and autoimmune responses need to be further identified. Methods: The characters and functions of human IL21‐AS1 and its mouse homologous lncRNA (mIl21‐AS) were investigated by a series of biochemical assays and cell transfection assay. mIl21‐AS1 regulating humoral immune response in vivo was explored by keyhole limpet haemocyanin (KLH) and chronic graft versus host disease (cGVHD) model. Results: Human IL21‐AS1 and its mouse homologous lncRNA (mIl21‐AS) were identified and cloned. We uncovered that IL21‐AS1 was highly expressed in CD4 + T cells of SLE patients and Tfh cells, which promoted differentiation of Tfh cells. Mechanistically, IL21‐AS1 bound heterogeneous nuclear ribonucleoprotein U and recruited acetyltransferases CREB‐binding protein to the promoter of IL21, leading to the transcriptional activation of IL21 and Tfh cells differentiation through increasing Histone H3 acetylation level on IL21 promoter. Moreover, Tfh proportion and antibodies production were significantly increased in mIl21‐AS knock‐in mice immunized with KLH. mIl21‐AS1 overexpression also exacerbated the lupus‐like phenotype in cGVHD mice model. Conclusions: Our results demonstrate that IL21‐AS1 activates IL21 transcription via epigenetic mechanism to promote germinal centre response, adding insight into the molecular regulation of autoimmune pathogenesis and providing a novel target for SLE treatment. Abstract : IL21‐AS1 was highly expressed in CD4 + T cells of SLE patients and Tfh cells specifically. IL21‐AS1 binds to the promoter of IL21 gene and interacts with hnRNPU and CBP protein to regulate H3 acetylation level in the promoter region of IL21 . IL21‐AS1 overexpression promotes IL21 transcription activation and the aberrant differentiation of Tfh cells in SLE patients, thereby exacerbating autoimmune phenotypes of SLE.